Rotatable Sphincterotome Facilitates Bile Duct Cannulation in Patients With Altered Ampullary Anatomy - Maluf-Filho, Fauze (Millennium Medical Publishing, 2008)
In patients who have undergone prior Billroth-II (B-II) anastomosis, endoscopic retrograde cholangiopancreatography (ERCP) is challenging due to altered duodenal anatomy, which requires use of customized sphincterotomes. We report the use of a standard rotat-able sphincterotome for successful cannulation in 5 patients with prior B-II gastrojejunostomy and 1 patient with choledochoduodenostomy. In our experience, cannulation and endoscopic intervention were successfully accomplished in all patients without any complications. Although retrospective case series analysis limits the conclusiveness of our findings, we believe that a rotatable sphincterotome can be successfully utilized to cannulate the common bile duct in patients with prior B-II anastomosis, thereby eliminating the need to maintain an inventory of specialized accessories.